Characterization of a Multiresistance Plasmid Carrying the optrA and cfr Resistance Genes From an Enterococcus faecium Clinical Isolate - Morroni, Gianluca; Brenciani, Andrea; Antonelli, Alberto; Maria D’Andrea, Marco; Di Pilato, Vincenzo; Fioriti, Simona; Mingoia, Marina; Vignaroli, Carla; Cirioni, Oscar; Biavasco, Francesca; Varaldo, Pietro E.; Rossolini, Gian Maria; et al. (Frontiers in Microbiology, 2018)
Enterococcus faecium E35048, a bloodstream isolate from Italy, was the first strain where the oxazolidinone resistance gene optrA was detected outside China. The strain was also positive for the oxazolidinone resistance gene cfr. WGS analysis revealed that the two genes were linked (23.1 kb apart), being co-carried by a 41,816-bp plasmid that was named pE35048-oc. This plasmid also carried the macrolide resistance gene erm(B) and a backbone related to that of the well-known Enterococcus faecalis plasmid pRE25 (identity 96%, coverage 65%). The optrA gene context was original, optrA being flanked by two transposase genes; this region was integrated into the gene encoding for the ζ toxin protein (orf19 of pRE25). The cfr gene was flanked by two ISEnfa5 insertion sequences and the element was inserted into an lnu(E) gene. Both optrA and cfr contexts were excisable. pE35048 oc could not be transferred to enterococcal recipients by conjugation or transformation. A plasmid-cured derivative of E. faecium E35048 was obtained following growth at 42°C, and the complete loss of pE35048-oc was confirmed by WGS. pE35048-oc exhibited some similarity but also notable differences from pEF12-0805, a recently described enterococcal plasmid from human E. faecium also co-carrying optrA and cfr; conversely it was completely unrelated to other optrA- and cfr-carrying plasmids from Staphylococcus sciuri. The optrA-cfr linkage is a matter of concern since it could herald the possibility of a co-spread of the two genes, both involved in resistance to last resort agents such as the oxazolidinones.